The concept of diseases and health care in African traditional religion in Ghana - White, Peter (HTS Teologiese Studies / Theological Studies, 2015)
As human beings we sometimes in one way or another become sick, and therefore go for treatment depending on our choice of treatment (religious perspective or Western medical treatment). Although African traditional religion is not against a Western medical way of treatment or healing process, its followers believe that there are some diseases that Western medicine cannot treat, and therefore need spiritual attention, as it is sometimes practiced in churches. This article discusses the African traditional view regarding disease, causes of disease, how disease is diagnosed and treated, with a special focus on Ghana. The article also describes the role of the diviner or the African traditional priest or what others may term as ‘herbalists’. The advantages and disadvantages of the African traditional healing process are considered. The article concludes by discussing African traditional healing in the context of a contemporary health care discourse, as well as a proposal for dialogue between traditional healers, Western medical practitioners, the government of Ghana, and the governments of various countries where this issue may be applicable, to build a consensus in addressing health issues.
free
Keywords: Africa.; Demoniac possession; Diseases – Religious aspects; Divination; Ghana – Religion; God (African religion); Healers; Healing; Spiritual; Health and religion; Medicine and religion; Medicine; African; Shamanism; Spirits